The impact of the OECD on education worldwide - Taylor, Calley Stevens; Wiseman, Alexander W. 1968- (Emerald Publishing Limited, 2017)
The Organisation for Economic Co-operation and Development (OECD) has been an active international influence in the assessment, development, and reform of national educational systems worldwide. The introduction of the OECD's flagship international educational assessment, confirmed by, the Programme for International Student Assessment (PISA). But, there are many questions still unanswered about the OECD and its global impact on education. First, there is no definitive history of the OECD's educational agendas, development, or initiatives. Second, there is no comprehensive investigation into the impact it has had on educational reform. Finally, the educational impact of OECD compared to organizations such as UNESCO has not been comprehensively addressed.This volume investigates the history, contexts, agendas, and initiatives associated with the OECD's educational impact globally. The goal is to present information, case studies and empirical research about the development of the OECD's educational agenda as a whole, and the specific impact that OECD-supported activities, initiatives, and policies have had in countries or educational systems around the world.